Determining the Climate Risk in the City Using the Risk Matrix Method - Examples from Poland - Wojciech Szymalski; Andrzej Kassenberg (Studia Ecologiae et Bioethicae)
The preparation of urban adaptation plans in Poland required application of tools, hitherto rarely used in geographical sciences. One of them is the risk matrix, the application of which originates from management science. The original application of the risk matrix is the business environment. The first prepared municipal plan for adaptation in Poland is The Climate Change adaptation strategy for the city of Warsaw by 2030 (The City of Warsaw 2019). The ongoing analytical work related to the preparation of this plan for adaptation was completed with the preparation of the draft strategy in 2017. The preparation of the draft took place during a workshop held with a group of stakeholders, called the Warsaw Climate Change Adaptation Roundtable (the so-called “WOSAK”). During this workshop, a risk matrix was used for the first time to determine climate risk in Warsaw. Subsequently, the method was used in other cities in Poland. This paper will present the basis for the application of the risk matrix method, in the assessment of a city’s climate risk. The results and evaluation of the application of the method in the city’s adaptation plans prepared so far by the team of the Institute for Sustainable Development Foundation, will also be presented.